Endoplasmic reticulum stress in human chronic wound healing: Rescue by 4‐phenylbutyrate. Issue 1 (22nd November 2020) - Bachar‐Wikstrom, Etty; Manchanda, Mansi; Bansal, Ritu; Karlsson, Magnus; Kelly‐Pettersson, Paula; Sköldenberg, Olof; Wikstrom, Jakob D.
Abstract: During wound healing, cells have a high rate of protein synthesis and many proteins need to be folded post‐translationally to function, which occurs in the endoplasmic reticulum (ER). In addition to proliferation, several cellular stress conditions, such as hypoxia, in the wound micro‐environment lead to the accumulation of unfolded or misfolded proteins in the ER, causing ER stress. Eukaryotic cells have a signalling system to manage ER stress called the unfolded protein response (UPR). Mild UPR activation has a beneficial homeostatic effect; however, excessive UPR induces cell death. Herein, we examined venous leg ulcer biopsies versus normal acute incisional wounds in age‐matched elderly subjects and found a large increase in ER stress markers. To study the underlying mechanism, we established several cell cultures from amputated legs from the elderly that showed inherent ER stress. While both keratinocytes and fibroblasts migration was impaired by ER stress, migration of elderly leg skin keratinocytes was markedly improved after treatment with the chemical chaperone and clinically established drug 4‐phenylbutyrate (4‐PBA) and demonstrated a reduction in ER stress markers. In a full‐thickness human skin wound healing model, 4‐PBA improved the reepithelialisation rate, which suggests it as a promising drug repurposing candidate for wound healing.